2011
DOI: 10.1016/j.jacc.2011.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Rho-Kinase Activity in Circulating Neutrophils of Patients With Vasospastic Angina

Abstract: These results indicate that Rho-kinase activity in circulating neutrophils is enhanced in patients with VSA and may be a useful biomarker for diagnosis and disease activity assessment of the vasospastic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 39 publications
5
51
0
1
Order By: Relevance
“…2 We have also recently demonstrated that Rho-kinase activity in circulating neutrophils is a useful biomarker for the diagnosis and disease activity assessment of VSA. 3 We thus examined whether Rho-kinase activity was increased in VSA patients after the Earthquake.…”
mentioning
confidence: 99%
“…2 We have also recently demonstrated that Rho-kinase activity in circulating neutrophils is a useful biomarker for the diagnosis and disease activity assessment of VSA. 3 We thus examined whether Rho-kinase activity was increased in VSA patients after the Earthquake.…”
mentioning
confidence: 99%
“…Nitrite oxide deficiency increases the susceptibility to potent vasoconstrictor mediators such as angiotensin II and endothelin I. Other precipitating factors are enhanced phospholipase C and Rho kinase activity (4,5). They regulate the intracellular calcium level and cause smooth muscle constriction.…”
Section: Discussionmentioning
confidence: 99%
“…Some observations regarding the role of the Rho/ROCK signaling pathway in humans indicate that systemic activation of ROCK is associated with many cardiovascular diseases [11,12]. Additionally, it has been reported that ROCK activity is associated with the number of components of the metabolic syndrome [13] and inflammation markers such as CRP and adiponectin.…”
Section: Increased Rock1 Activity In Stemi Patients With Dmmentioning
confidence: 99%